Texas! Lucky [compact disc, unabridged] - Brown, Sandra, 1948- (Random House Audio, 2008)
Lucky Tyler attracted trouble - and women - like a lightning rod. On the night he stepped in to rescue a mysterious redhead in a seedy bar, he got more than he bargained for! The lady excited him, challenged him, drove him wild with desire, then vanished without a trace. Lucky was desperate to find her, to brand her with his heat - and when the police were called in to investigate a suspicious fire at Tyler Drilling, his family business, he needed her for an alibi.